AB0446 REAL-LIFE USE OF BARICITINIB IN RHEUMATOID ARTHRITIS: A MULTICENTER OBSERVATIONAL STUDY OF 150 PATIENTS. (June 2019) - Guidelli, Giacomo Maria; Generali, Elena; Bazzani, Chiara; Gorla, Roberto; Sakellariou, Garifallia; Limonta, Massimiliano; Chimenti, Maria Sole; Perricone, Roberto; Conticini, Edoardo; Frediani, Bruno; Boffini, Nicola; Dagna, Lorenzo; et al.
Abstract : Background: Baricitinib is an oral selective JAK1/2 inhibitor recently approved in the EU for the treatment of rheumatoid arthritis (RA). No real-life data are available about its efficacy and safety. Objectives: To investigate the efficacy and safety profiles of baricitinib in a real-life setting. Methods: We performed a multicenter prospective observational study on adult RA patients starting JAK inhibitors between 12/2017 and 12/2018. Demographic and clinical data as well as laboratory values and adverse events were collected at baseline and after 12 and 24 weeks. Disease activity was measured by DAS28-CRP at baseline, after 12 and 24 weeks. Results: We obtained data from 150 patients with RA (women 116 – 77.3%; median age 60 years, inter-quartile range IQR 54-68; median disease duration 10 years, IQR 4-18) treated with baricitinib 2 or 4 mg QD, however only 2/150 (1.3%) at the reduced dosage. At the time of database lock 95/150 (63%) patients have completed the 12 weeks follow-up, 38/150 (25%) patients have completed the 24 weeks follow-up. Baricitinib was started after at least one conventional synthetic DMARD in all 148/150 cases (99%), being in all of cases methotrexate, while was started prior to a biologic DMARD in 57 (38%) patients. It was prescribed as a second line in 17/93 (18%) patients, third in 27 (29%), fourth or higher in 49 (53%). Baricitinib was prescribed as monotherapy in 57/150 (38%) patients, while combined with methotrexate in 65/150 (43%), at a median dosage of 15 mg/week. Oral corticosteroids were used by 105/150 (70%) patients, at a median dosage of 5 mg/day. Mean DAS28-CRP at baseline was 4.92 (standard deviation 1.22), with 65 (43.3%) patients having a DAS28-CRP>5.1. At both 12 and 24 weeks, a significant reduction of disease activity scores was observed (DAS28-CRP mean 3.07, SD 1.36, and 2.85, SD 1.35, respectively; p values<0.001). Sixteen (11%) patients discontinued the treatment, with 8 (50%) due to primary inefficacy, mainly in the first 3 months of therapy (5/8– 63%). Adverse events were observed in 19/150 (13%) patients, 7 being non-serious infections (4 upper respiratory tract infections, 2 urinary tract infection, 1 Herpes labialis ), while 3 patients manifested Herpes Zoster reactivation, 2 deep vein thrombosis (one with pulmonary embolism), 2 discontinued due to severe anemia and pancytopenia, and 2 developed self-limiting liver enzymes elevation. Conclusion: In our real-world dataset, baricitinib is effective in reducing RA disease activity, after 12 weeks, being generally well-tolerated with few severe adverse events. Disclosure of Interests: Giacomo Maria Guidelli: None declared, Elena Generali: None declared, Chiara Bazzani: None declared, Roberto Gorla: None declared, Garifallia Sakellariou: None declared, Massimiliano Limonta: None declared, Maria Sole Chimenti: None declared, Roberto Perricone: None declared, Edoardo Conticini: None declared, Bruno Frediani: None declared, nicola boffini: None declared, Lorenzo Dagna Consultant for: Prof Lorenzo Dagna received consultation honoraria from Abbvie, Amgen, Biogen, Bristol-Myers Squibb, Celltrion, Novartis, Pfizer, Sanofi-Genzyme, and SOBI., Marta Riva: None declared, Maria Rosa Pozzi: None declared, Rosa Daniela Grembiale Grant/research support from: BMS, Consultant for: JANSSEN, CELGENE, Speakers bureau: PFIZER, JANSSEN, BMS, NOVARTIS, Teodora Serban: None declared, Gerolamo Bianchi Consultant for: Alfa-Sigma, Amgen, BMS, Celgene, Medac, UCB, Speakers bureau: Abbvie, Abiogen, Alfa-Sigma, Amgen, BMS, Celgene, Carlo Selmi Grant/research support from: Abbvie, Janssen, MSD, Novartis, Pfizer, Consultant for: Abbvie, Alfa-Sigma, Biogen, BMS, Celgene, Eli-Lilly, GSK, Janssen, Merck Sharp and Dohme, Novartis, Pfizer, Roche, Sanofi-Genzyme, YCB, Speakers bureau: Abbvie, Alfa-Sigma, Biogen, BMS, Celgene, Eli-Lilly, GSK, Janssen, Merck Sharp and Dohme, Novartis, Pfizer, Roche, Sanofi-Genzyme, YCB